A Facile Procedure for the Conversion of Oximes to Ketones and Aldehydes with Potassium Dichromate in Dimethylformamide under Homogeneous Conditions. Issue 4 (2012) - Huang, Li-Hong; Lou, Ji-Dong; Zhang, Changhe; Lin, Fang; Zou, Xiao-Nan
Abstract : Oxidative cleavage of oximes to their parent corresponding carbonyl compounds using potassium dichromate-dimethylformamide system under homogeneous conditions in good yields is described. The main advantage of the present method is no need of preparation of hexavalent chromium-based reagents due to using a polar aprotic solvent.